Circulating ceramide ratios and risk of vascular brain aging and dementia. Issue 2 (16th January 2020) - McGrath, Emer R.; Himali, Jayandra J.; Xanthakis, Vanessa; Duncan, Meredith S.; Schaffer, Jean E.; Ory, Daniel S.; Peterson, Linda R.; DeCarli, Charles; Pase, Matthew P.; Satizabal, Claudia L.; Vasan, Ramachandran S.; Beiser, Alexa S.; et al.
Abstract: Background: We determined the association between ratios of plasma ceramide species of differing fatty‐acyl chain lengths and incident dementia and Alzheimer's disease (AD) dementia in a large, community‐based sample. Methods: We measured plasma ceramide levels in 1892 [54% women, mean age 70.1 (SD 6.9) yr.] dementia‐free Framingham Offspring Study cohort participants between 2005 and 2008. We related ratios of very long‐chain (C24:0, C22:0) to long‐chain (C16:0) ceramides to subsequent risk of incident dementia and AD dementia. Structural MRI brain measures were included as secondary outcomes. Results: During a median 6.5 year follow‐up, 81 participants developed dementia, of whom 60 were diagnosed with AD dementia. In multivariable Cox‐proportional hazards analyses, each standard deviation (SD) increment in the ratio of ceramides C24:0/C16:0 was associated with a 27% reduction in the risk of dementia (HR 0.73, 95% CI 0.56–0.96) and AD dementia (HR 0.73, 95% CI 0.53–1.00). The ratio of ceramides C22:0/C16:0 was also inversely associated with incident dementia (HR per SD 0.75, 95% CI 0.57–0.98), and approached statistical significance for AD (HR 0.73, 95% CI 0.53–1.01, P = 0.056). Higher ratios of ceramides C24:0/C16:0 and C22:0/C16:0 were also cross‐sectionally associated with lower white matter hyperintensity burden on MRI (−0.05 ± 0.02, P = 0.02; −0.06 ± 0.02, P = 0.003; respectively per SD increase), but not with other MRI brain measures. Conclusions: Higher plasma ratios of very long‐chain to long‐chain ceramides are associated with a reduced risk of incident dementia and AD dementia in our community‐based sample. Circulating ceramide ratios may serve as potential biomarkers for predicting dementia risk in cognitively healthy adults.